Drug Delivery Systems for Prevention and Treatment of Osteoporotic Fracture - Nazrun Shuid, Ahmad; Izzah Ibrahim, Nurul; Cairul Iqbal Mohd Amin, Mohd; Naina Mohamed, Isa (Current Drug Targets, 2013)
Anti-osteoporotic drugs are available for treatment of osteoporosis and for preventing osteoporosis complications especially fractures. Most of the current anti-osteoporotic drugs are administered orally or parenterally to target the osteoporosis-affected bones. However, bone is a peripheral organ with limited blood supply. Therefore, the drugs delivered are exposed to various physicochemical and biological factors which affect the bioavailability of the drugs. In preclinical research, the dose of a potential anti-osteoporotic agent used in animal model may be too high for human application when administered via the conventional route of administration. The current anti-osteoporotic drugs need to be administered at higher doses to account for pharmacological interactions. However, this will expose the patients to adverse effects such as the cancer risks of postmenopausal women who took estrogen replacement therapy. There is also problem with patient compliance as anti-osteoporotic drugs may have to be taken for prolonged duration. The current deliveries of drugs need to be improved to overcome these problems. This review discussed several potential drug delivery systems which are able to contain the anti-osteoporosis drugs and release them slowly to the targeted bone. Among them are various carriers, polymers and microsponges, which may not only increase drug efficacy but also reduce adverse effects. The delivery systems allow the drugs to be administered locally at the targeted bone for longer duration, therefore reducing drug frequency and improving patient’s compliance. It is hoped that these delivery systems may be applicable for the treatment of osteoporosis in the future to keep tab of the rising osteoporotic fracture incidence.
Keywords: Bone